Nutri-garden for nutritional security and diversity: Some insights from POSHAN Abhiyan - R C Agrawal; Lipi Das; Rajni Jain; Prabhat Kishore; V R Nikam; Mridula Devi (Agricultural Economics Research Review, 2024)
To combat the challenges of malnutrition, the government initiatives such as the POSHAN Abhiyan are emphasized, particularly the introduction of Poshan Vatika (Nutri-Gardens), which is on empowering the women to cultivate nutritious foods and enhance quality of family diets. Data from 1710 farm families across 12 states, has been analyzed through Partial Least Squares Path Modelling and logistic regression, indicates that Nutri-Gardens positively impact the family nutrition. In conclusion, Nutri-Gardens offer a holistic approach to improving nutrition in rural India, empowering women, raising their socio-economic status, and promoting nutrition education and community participation. The collaboration among various stakeholders is essential to disseminate information effectively and ensure the success and sustainability of Nutri-Gardens as a cost-effective and sustainable approach to mitigate malnutrition in the rural households.